Colonic cryptococcosis presenting with chronic diarrhea in a person with advanced human immunodeficiency virus disease: a case report - Oh, Hyunjoo; Kim, Misun; Yoo, Jeong Rae; Boo, Sun-Jin; Heo, Sang Taek (Journal of medicine and life science, 2022)
Cryptococcus neoformans infection usually occurs in patients with advanced human immunodeficiency virus (HIV) infection or with a CD4 T lymphocyte count of <100 cells/μL. Pulmonary and central nervous system infections are the most frequently encountered forms of cryptococcosis; however, colonic cryptococcosis is uncommon. We describe the case of a 41-year-old antiretroviral-naïve man with HIV infection diagnosed eight years prior and intermittent diarrhea for 4 months who presented to the emergency department with a 1-day history of low-grade fever and confusion. Brain magnetic resonance imaging and cerebrospinal fluid analysis revealed normal results; however, he was diagnosed with Pneumocystis jirovecii pneumonia based on chest computed tomography and bronchoalveolar lavage analysis. Trimethoprim-sulfamethoxazole administration was initiated followed by antiretroviral treatment. Although his condition gradually improved, he developed fever and abdominal discomfort, and the diarrhea worsened. Endoscopy revealed a small ulcer in the distal transverse colon. Histopathological examination of a colon tissue sample revealed cryptococcal infection. He improved substantially during liposomal amphotericin B and fluconazole treatment. We encountered a rare case of colonic cryptococcosis that caused chronic diarrhea in a patient with advanced HIV infection. Colonic cryptococcosis should be considered when patients with acquired immune deficiency syndrome present with gastrointestinal symptoms.